Zoroastrians in early Islamic history accommodation and memory - Magnusson, Andrew David (Edinburgh Edinburgh University Press, 2023)
Examines debates about the inclusion or exclusion of Zoroastrians in Islamic society circa 600-1000 C.E
Keywords: Zoroastrianism -- Relations -- Islam; Islam -- Relations -- Zoroastrianism; Zoroastrians -- History; Zoroastrianism -- History; Zoroastrianism -- Relations -- Islam; Islam -- Relations -- Zoroastrianism; Zoroastriens - Histoire; Zoroastrisme - Histoire; Zoroastrisme - Relations - Islam; Islam - Relations - Zoroastrisme; Interfaith Relations; Islam; Zoroastrianism; Zoroastrians; Zoroastrians - History; Zoroastrianism - History; Zoroastrianism - Relations - Islam; Islam - Relations - Zoroastrianism; History